Karakteristik Iklim Mikro Dan Produksi Jagung Manis Pada Beberapa Sistem Tanam - Risa Wentasari; Rizka Novi Sesanti (Jurnal Penelitian Pertanian Terapan, 2016)
The purpose of this study was to determine the characteristics of the micro-climate(temperature, humidity, and light intensity) and the production of sweet corn on a sigle row,doble row, twin row, and Twin seed planting system. This study was conducted in anexperimental garden of Politeknik Negeri Lampung, Hajimena South Lampung, in July-September, 2015. This study is based on randomized block design with one factor croppingsystem consists of 4 treatment ie : Sigle Row (SR) (20cm x 75cm), Doble Row ( DR ) (20cm x20cm x 80 cm), Twin Row (TR) (20cm x 10cm x 80 cm) , and Twin Seed (TS) with plantSpacing (40cm x 75cm 2 seed in one planting hole). Parameter observations of this studyconsisted of (1) micro-climate (temperature (oC), relative humidity (RH %) and Interceptionof Light (%) ) and (2)production (corn length (cm) , corn diameter (m ) and Corn weights(grams). The data were analyzed using the F test at 1 % and 5 % level and than followed bytest BNT. The conclusion of this study were (1) The characteristics of the microclimate : a)There is a noticeable difference in the temperature of the top of the current crop of 4 mst andat 9 mst there is a significant difference in the temperature of the bottom , where SR has adifferent temperature involves the other b) All systems planting has a relative humidity (%)were not significantly different , and c ) there is a difference light interception ( % ) duringthe day when 4 mst , where the twins seed has a light interception is different from othertreatments and there is a difference light interception during 9 mst where sigle row has adifferent light interception to other treatments. (2) The production of sweet corn on thetreatment SR, DR, TR and TS were not significantly different and has a weight of corn (SR =354.8 grams, DR = 316.5 grams, 328.5 grams TR and TS = 325.4 grams) same withdescription bonanza varieties (270-300 grams).Keywords : Cropping Systems , Micro Climate , Production